The causal loop diagram model of flood management system based on eco-drainage concept - Rahmawati Fitria; Henita Rahmayanti; Bagus Sumargo (Sustinere: Journal of Environment and Sustainability, 2022)
Flooding has been a recurrent problem in the Indonesian capital, especially in the northern part of Jakarta, along the Jakarta shore. The floods were caused by a number of sources. According to Renald et al. (2016), there are four critical factors in designing disaster-prone cities in Indonesia, namely spatial management, disaster adaptation, disaster mitigation, and technology innovation. Therefore, the development of infrastructure in Jakarta has started to use these four elements, by applying the concept of environmentally friendly drainage, specifically the concept of eco-drainage. This study aims to understand the general picture through the cause-and-effect relationship between all flood components. This study used a qualitative approach and was conducted using a dynamic system method to describe the Causal Loop Diagram (CLD) model, which provides information between interrelated variables and forms a complex system Rifaldi et al. (2021). The model generated from the dynamic system can be used for scenario analysis by showing how the interactions between the components that make up the structure of the system and the effects of feedback loops affect. The CLD model shown shows that the use of eco-drainage will directly affect the condition of 2 (two) other variables, both of which will lead to one main variable. The proposed settlement scenarios will result in policy and technical recommendations. This CLD model shows that the interaction between variables is very dynamic and affects each other massively and holistically. Combining dynamic system processes with SMWW can potentially improve the expected results in engineering and provide an alternative scenario.